A novel ceramic tubular membrane coated with a continuous graphene-TiO2 nanocomposite thin-film for CECs mitigation - Presumido, Pedro Henrique (2022)
This work presents a ceramic tubular membrane coated with a continuous graphene-TiO2 nanocomposite thinfilm for contaminants of emerging concern (CECs) removal from synthetic and real matrices in single-pass flow-through operation. Microfiltration ceramic membranes were coated in situ with graphene (G)-TiO2-P25 nano-composite using two different methods: Membrane type A - TiO2-P25 incorporated in the G preparation stage (1% [MA-1], 2% [MA-2] and 3% [MA-3] [w/v]), and Membrane type B - TiO2-P25 thin-film uniformly coated over the G film surface (coating layers: 3 [MB-1], 6 [MB-2], and 9 [MB-3]). After the catalyst deposition and before the pyrolysis step, air was forced to pass through the membranes pores (inside-outside mode), providing a porous film. The CECs solution (diclofenac-DCF, 17β-estradiol-E2, 17α-ethinylestradiol-EE2 and amoxicillin-AMX) was prepared using Ultrapure water (UPW) or an urban wastewater after secondary treatment (UWW) fortified with 500 μg L 1 of each CEC. Membranes were characterized by the following techniques: Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Fourier-Transform Infrared spectroscopy (FTIR), Diffuse Reflectance UV-Visible spectroscopy (DR UV-Vis) and Raman spectroscopy. The membranes coated with MA-3 and MB-2 catalyst films, irradiated by UVA light, showed the highest ability for CECs removal. Furthermore, the Relative flux reduction ratio (RFR) decreased around 45% in the absence of UVA light, owing to membrane fouling. The combination of filtration and oxidation (G-TiO2-UVA) provided a permeate with higher quality and minimized membrane fouling. Although membrane type B allowed for a permeate with higher quality, membrane type A provided a higher permeate flux.